Ulcero-mutilating acropathy disease - Danza, Franco; Wettstein, Juana M; Sáez, Hugo (Cirugía del Uruguay, 1975)
The authors report an ulcero-mutilant acropathy of sporadic incidence. Its primary characteristics were the loss of pain perception in both lower limbs and important trophic abnormalities of their distal area. Angiograms were normal and there was no diabetes. The response to sympathectomy was satisfactory. A lesion of the sympathetic ganglia with a deficitary back ground seems to explain the pathogenesis of this case.